2017
DOI: 10.14393/bj-v33n3-34547
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of the economic viability of feedlot aberdeen angus steers fed with different proportions of concentrate

Abstract: ABSTRACT:The economic viability of feedlot Aberdeen Angus steers fed with diets composed of different concentrate levels (CL) in dry matter (25, 40, 55 or 70%) was estimated using Monte Carlo simulation combined with Spearman rank correlation, considering nine random input variables, as well as stochastic dominance (DOM) and sensitivity (SENS) analyses. For the financial indicator simulation, net present value (NPV), cash flow with indicators of performance, and the probability distribution of all cost and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(20 reference statements)
2
3
0
2
Order By: Relevance
“…Prices of unfinished and finished cattle and final weight were the most important items. This finding was in line with other probabilistic sensitivity analyses of feedlot cattle (PACHECO et al, 2014a(PACHECO et al, , 2014b(PACHECO et al, , 2014c(PACHECO et al, , 2017ROSA et al, 2017;SILVA et al, 2017).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Prices of unfinished and finished cattle and final weight were the most important items. This finding was in line with other probabilistic sensitivity analyses of feedlot cattle (PACHECO et al, 2014a(PACHECO et al, , 2014b(PACHECO et al, , 2014c(PACHECO et al, , 2017ROSA et al, 2017;SILVA et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…SILVA et al, (2017) stated that, from an economic point of view, studies involving stochastic simulation in livestock production systems are limited, specially with respect to the refinement of methods aimed to improve the quality of simulations results. ROSA et al, (2017) draw attention to the fact that feedlot beef cattle require high volume of financial resources at the beginning of the investment project implementation, which justifies the use of simulation techniques to help in decision making on the part of investors.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficients of finished steer price, steer price and silage price were 1.42, -1.18 and 0.76, respectively. The great impact of finished steer price and steer price on economic performance corroborated other findings (RoSa et al, 2017). The identification of these sources of risk helps in the design of preventive strategies, such as the use of forward contracts for finished cattle (CARRER et al, 2013).…”
Section: Yearsupporting
confidence: 71%
“…Most of the studies addressing the economic viability of feedlot-finished cattle focused on the roles of diet composition (MISSIO et al, 2009;PACHECO et al, 2014a;ROSA et al, 2017) and slaughter weight (PACHECO et al, 2014b(PACHECO et al, , 2015FABRICIO et al, 2017), probably because the purchases of cattle and feed represent approximately 87% of TOC. Studies about the effects of space allowance are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Although the three pen space allowances were considered economically satisfactory, higher NPV per animal is preferable. Previous studies showed that the NPV for confined cattle in Brazil varied from R$ 43.20 to R$ 594.00, depending on the levels of concentrate in the diet and slaughter weights (PACHECO et al, 2015;BARBIERI et al, 2016;ROSA et al, 2017).…”
Section: Resultsmentioning
confidence: 99%